Comparison of toxicity and cellular responses following pulmonary exposure to different types of nanofibers. Issue 9 (26th November 2022) - Kang, Min-Sung; Lee, Gwang-Hee; Yang, Mi-Jin; Sung, Myeong-Chang; Han, Hyoung-Yun; Lee, Byoung-Seok; Baek, Bosung; Kim, Dong-Wan; Park, Eun-Jung
Abstract: Pulmonary effects of inhaled microfibers are an emerging public health concern. In this study, we investigated toxicity following pulmonary exposure to synthetic polyethylene oxide fibroin (PEONF) and silk fibroin (SFNF) nanofibers and the cellular responses. When instilled intratracheally weekly for four weeks, body weight gain was significantly reduced in female mice exposed to the higher dose of SFNF when compared with the control group. The total number of cells in the lungs was more significant in all treated groups than in the control, whereas the relative portion of neutrophils and eosinophils increased significantly only in female mice exposed to SFNF. Both types of nanofibers induced notable pathological changes and increased pulmonary expression of MCP-1α, CXCL1, and TGF-β. More importantly, blood calcium, creatinine kinase, sodium, and chloride concentration were affected significantly, showing sex- and material-dependent differences. The relative portion of eosinophils increased only in SFNF-treated mice. In addition, both types of nanofibers induced necrotic and late apoptotic cell death in alveolar macrophages after 24 h of exposure, with accompanying oxidative stress, increased NO production, cell membrane rupture, intracellular organelle damage, and intracellular calcium accumulation. Additionally, multinucleated giant cells were formed in cells exposed to PEONF or SFNF. Taken together, the findings indicate that inhaled PEONF and SFNF may cause systemic adverse health effects with lung tissue damage, showing differences by sex- and material. Furthermore, PEONF- and SFNF-induced inflammatory response may be partly due to the low clearance of dead (or damaged) pulmonary cells and the excellent durability of PEONF and SFNF.